Perlindungan Hukum Bagi Korban Tindak Pidana Terorisme di Indonesia: Tantangan dan Implementasi - Nuralam, Yoga Wibawa; Saleh, Moh. (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study aims to explore the legal protection provided to victims of terrorism in Indonesia, considering its broad impact on individuals and society. Using a normative juridical method, the study analyzes regulations such as Law No. 5 of 2018 and Law No. 13 of 2006, along with relevant legal concepts. The findings indicate that while legal protection includes compensation, restitution, and rehabilitation, its implementation faces challenges in legal, policy, and institutional coordination aspects. This study contributes by identifying key obstacles in regulatory enforcement and proposing strategies to enhance the effectiveness of legal protection through optimized law enforcement mechanisms. The study's limitation lies in its focus on normative analysis without an in-depth empirical examination. Its originality stems from a comprehensive evaluation of the effectiveness of existing regulations and strategic recommendations to improve protection for terrorism victims.